Food Balance Analysis in An Effort to Maintain Food Stability in Lubuklinggau City: – - Utomo, Rohadi; Christnawan, Dimas Bryanputra; Muhammad, Syarif Kavi (University of Jember, 2024)
Food is a basic need whose demand continues to increase along with population growth. The most important issue of food security is how the state reaches out to various regions or interested parties and makes efforts to strengthen food security. This research aims to determine the picture of the food situation in Lubuklinggau City in 2022 with the hope that it can be used as a basis for determining policies to maintain the stability of food availability in Lubuklinggau City. The type of data used in this research is Lubuklinggau City Foodstuffs Balance (NBM) data for 2022, sourced from the Lubuklinggau City Food Security Service, which was quoted in 2023. The data was analyzed using a quantitative description. The results of this research, namely the Food Material Balance (NBM) Analysis of Provisional Figures (ASEM) for Lubuklinggau City in 2022, show a total energy availability of 2,392 Cal/cap/day, protein 63.4 grams/cap/day, and fat 79 grams/cap/day. This data shows that there have been several increases and some decreases compared to the 2021 Fixed Figure Food Ingredient Balance (ATAP). Judging from the Expected Food Pattern Score, it is explained that several food groups have reached the adequacy desirable dietery pattern (PPH), starting from the grain group, oils and fats, sugar, and vegetable and fruit groups with varying deficit and surplus values.